A class of semisymmetric graphs - Wang, Li (Ars mathematica contemporanea, 2014)
A simple undirected graph is said to be semisymmetric if it is regular and edge-transitive but not vertex-transitive. Every semisymmetric graph is a bipartite graph with two parts of equal size. Let ?$p$? be a prime. In this paper, a class of semisymmetric graphs of order ?$2p^3$? are determined. This work is a partial result for our long term goal to classify all semisymmetric graphs of order ?$2p^3$?.
Keywords: grupe; permutation group; primitive group; semisymmetric graph; teorija grafov; vertex-transitive graph